THE CHESTER BEATTY PAPYRUS AND THE WESTERN AND BYZANTINE TEXTS - Tarelli, C. C. (The journal of theological studies, 1940)
C. C. TARELLI; THE CHESTER BEATTY PAPYRUS AND THE WESTERN AND BYZANTINE TEXTS, The Journal of Theological Studies, Volume os-XLI, Issue 163-164, 1 July 1940, Pa